Pencapaian Kemampuan Low Order Thinking Siswa antara Pembelajaran Probing Prompting dan Matematika Realistik - Dumaria Theresia; Mohammad Syafi’i; Niken Vioreza (Pendidikan Matematika STKIP Kusuma Negara, 2020)
Not infrequently when students are dealing with mathematics problems where they do not know what they are supposed to do. Learning in class can make a habituation to students. This study aims to determine whether or not there are differences in achievement of students' Low Order Thinking (LOT) abilities between learning Probing Prompting (PP) and Realistic Mathematics (MR) on quadrilateral. This research was conducted with a total sample of 60 students, namely 30 students in class VIIA with PPL learning and 30 students in class VIIB with MR learning. The sample selection is done by cluster random sampling. The instruments used to collect data are based on three dimensions in the cognitive domain, namely remembering, understanding, and applying. The results of the descriptive statistical analysis of the data show that the average achievement of students in the PP learning group is equal to 75.36, while the average achievement of students in the MR group is equal to 68.53. Based on the results of data analysis, it was concluded that there were significant differences in the LOT achievement of students between PP and MR learning on Quadrilateral material.